The effect of caloric restriction on genetical pathways - Mustafa Fevzi Karagöz; A. Gülçin Sağdıçoğlu Celep (Food Science and Human Wellness)
Energy restriction is defined as reducing nutrient intake without dragging the organism into malnutrition. Energy restriction is preferred because it is a non-genetic intervention that increases life expectancy. Nicotinamide adenine dinucleotide (NAD+) and adenosine monophosphate (AMP) levels, which are the indicators of intracellular energy deficiency, increase with energy restriction. The increase in NAD+ level stimulates sirtuin (SIRT) enzymes, and the increase in AMP level stimulates AMP-activated protein kinase (AMPK). Various mechanisms are regulated by stimulating these enzymes. By Forkhead box O (FoxO) transcription factors, the ability of resistance to oxidative stress increases, and antioxidant genes, DNA repair, and autophagy genes are stimulated. Apoptosis is induced by stimulation of the p53 protein, and tumor growth is suppressed by the disruption of aging cells. The suppression of phosphoinositide 3-kinase (PI3K)-/-Akt, and therefore mTOR signal stimulates autophagy and mitophagia, and cleanses damaged cells and organelles. Mitochondrial biogenesis is stimulated, antioxidant capacity increases, and inflammatory response decreases. Adipose tissue and lipid metabolism are regulated by the regulation of fatty acid synthesis and oxidation. As a consequence, the effects of caloric restriction on cellular metabolism are regulated through the genetic pathways.